1998
DOI: 10.4141/s97-018
|View full text |Cite
|
Sign up to set email alerts
|

In situ amelioration of sodic minespoil with chemical amendments and crop management: II. Soil physical properties, soil moisture and plant growth

Abstract: . 1998. In situ amelioration of sodic minespoil with chemical amendments and crop management: II. Soil physical properties, soil moisture and plant growth. Can. J. Soil Sci. 78: 667-674. The effects of sulfur and gypsum amendments in conjunction with crop management (fallow/barley and forage) on soil physical properties, soil moisture and vegetation characteristics were measured on a sodic and calcareous sandy loam minespoil at the Highvale coal mine, west of Edmonton, Alberta.Amendment and crop management had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Since 2 MPa is considered the critical value of mechanical impedance for root growth (Taylor et al, 1966, taken from Levy andSumner, 1998;Bedard et al, 1997;Sansom et al, 1998;Ringrose-Voase et al, 2000), it was concluded that all treatments exhibited a high to very high surface compaction. As well, all the treatments exhibited some reduction in crop emergence.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2 MPa is considered the critical value of mechanical impedance for root growth (Taylor et al, 1966, taken from Levy andSumner, 1998;Bedard et al, 1997;Sansom et al, 1998;Ringrose-Voase et al, 2000), it was concluded that all treatments exhibited a high to very high surface compaction. As well, all the treatments exhibited some reduction in crop emergence.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, these parameters were integrated to understand the effects of amendment use and crop management on sodic minespoil amelioration along with their implications for successful reclamation of sodic surface-mined soils. Results from the study are reported in this and a companion paper (Sansom et al 1998). In the companion paper, the effects of chemical amendments and crop management on soil physical properties, soil water regime and plant growth are addressed.…”
mentioning
confidence: 85%
“…This significant difference was also evident in 1995 for Mg 2+ , but only in the LAM and UNAM layers. These results were attributed to additional soil water in the fallow/barley subplots (Sansom et al 1998) which increased leaching and removal of salts from the root zone. In 1995, only Cl -concentration was not significantly different between crop management treatments at any depth interval.…”
Section: Solutesmentioning
confidence: 98%
“…Nitrogen cycling (Fyles 1984) became better understood. Amendments such as gypsum and sulfur were used to reduce sodicity (Sansom et al 1998a(Sansom et al , 1998b. Fly ash chemistry and minerology were studied by Warren (1983).…”
Section: Soil Reclamation Researchmentioning
confidence: 99%